2007
DOI: 10.1161/circulationaha.106.678474
|View full text |Cite
|
Sign up to set email alerts
|

CXCR6 Promotes Atherosclerosis by Supporting T-Cell Homing, Interferon-γ Production, and Macrophage Accumulation in the Aortic Wall

Abstract: Background-T lymphocytes are thought to be important in atherosclerosis, but very little is known about the mechanisms of lymphocyte recruitment into atherosclerosis-prone aortas. In this study we tested the hypothesis that CXCR6, a chemokine receptor that is expressed on a subset of CD4 ϩ T helper 1 cells and natural killer T cells, is involved in lymphocyte homing into the aortic wall and modulates the development and progression of atherosclerosis. Methods and Results-To investigate the role of CXCR6 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 38 publications
6
91
1
Order By: Relevance
“…17 We found that CXCL16 is expressed both in regenerating muscle and in infiltrating, Mac-2 positive macrophages ( Figure 1). It is known that the receptor for CXCL16, CXCR6, is present in inflammatory cells, 36,37 and we found its expression is increased in regenerating muscle. These results are compatible with our hypothesis that CXCL16 influences the infiltration of inflammatory cells into injured muscle (Figure 1).…”
Section: Discussionmentioning
confidence: 61%
“…17 We found that CXCL16 is expressed both in regenerating muscle and in infiltrating, Mac-2 positive macrophages ( Figure 1). It is known that the receptor for CXCL16, CXCR6, is present in inflammatory cells, 36,37 and we found its expression is increased in regenerating muscle. These results are compatible with our hypothesis that CXCL16 influences the infiltration of inflammatory cells into injured muscle (Figure 1).…”
Section: Discussionmentioning
confidence: 61%
“…Recent data from studies using mice deficient in either CXCR6 or CXCL16 support a role for both ligand and receptor in atherogenesis [25,26]. Antagonism of the CXCR6:CXCL16 interaction may therefore be of therapeutic potential and a greater understanding of the molecular basis underlying this interaction is highly desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have suggested the proatherogenic role of CXCL16, and it has been shown that the expression of CXCL16 is enriched in the atherosclerotic plaques of humans and murine experimental models of atherosclerosis 11,12) . The absence of the CXCR6 gene attenuates atherosclerosis and decreases the percentage of CXCR6 T-cells within the aortic wall, thus indicating the proatherogenic role of the CXCL16-CXCR6 axis 13) . Despite this evidence, a recent rodent study suggested the atheroprotective effect of CXCL16 14) , and the plasma sol-CXCL16 levels have been reported to be decreased in patients with coronary atherosclerosis 15) .…”
Section: Ultrasound Assessment Of the Carotid Arteriesmentioning
confidence: 99%